1979
DOI: 10.1007/bf00005529
|View full text |Cite
|
Sign up to set email alerts
|

Parent-touching behavior by young fishes: incidence, function and causation

Abstract: SynopsisParent-touching behavior by young fishes occurs in a number of species. Most reports have been from the family Cichlidae, but this may reflect the major concentration of studies on these species. The behavior appears to serve a trophic function in many species, but may also serve to maintain cohesion of family groups, to keep adults in a parental state, or to communicate the motivational state of the young (e.g. fear, hunger). It has been suggested that prolactin may regulate the behavior and epidermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 97 publications
0
26
0
Order By: Relevance
“…LoVullo et al (1992) provided observations of parental male catfish (Bagrus meriodionalis) exposing their broods to invertebrates by spitting the food into the nest. Other likely examples could be the many cases of trophic provisioning in catfish and cichlids (Noakes 1979). Also in coral reefs, some juvenile fish swim with (unrelated) conspecifics after recruitment from their pelagic stage and could therefore also learn what and where to eat by observing conspecifics.…”
Section: Social Learning and Traditionmentioning
confidence: 99%
“…LoVullo et al (1992) provided observations of parental male catfish (Bagrus meriodionalis) exposing their broods to invertebrates by spitting the food into the nest. Other likely examples could be the many cases of trophic provisioning in catfish and cichlids (Noakes 1979). Also in coral reefs, some juvenile fish swim with (unrelated) conspecifics after recruitment from their pelagic stage and could therefore also learn what and where to eat by observing conspecifics.…”
Section: Social Learning and Traditionmentioning
confidence: 99%
“…According to Chong et al (2005) amino acids and essential substances in the mucus are extremely important in the early days of larval development. This same behavior is also known in neotropical species of S. discus, midas cichlid Cichlasoma citrinellum (Günther, 1824) and in two species from Madagascar and India; orange chromide Etroplus maculatus (Bloch, 1795) and pearlspot E. suratensis (Bloch, 1790) lineage (Hildemann 1959;Noakes 1979;Noakes and Barlow 1973;Ward and Wyman 1977). According to Buckley et al (2010), males are generally darker than females and therefore the larvae feed more with the former (Buckley et al 2010).…”
Section: Discussionmentioning
confidence: 57%
“…is also widespread -at least 28 species have been reported to exhibit fry mucus-feeding behaviour in four families (Noakes, 1979), and this behaviour has evolved many times, in species separated on distant branches of the fish phylogeny, including the Osteoglossiforme Arapaima gigas (Liiling, 1964;Menezes, 1951).…”
mentioning
confidence: 99%
“…are feeding on the mucus secreted by their parents (Chong et al, 2005;Noakes, 1979;Perrone and Zaret, 1979) [see also Hildemann (Hildemann, 1959) and references therein], it has also been shown that, in contrast to mammals, mucus is not the only meal they are getting. Critically, Bremer and Walter (Bremer and Walter, 1986) found that there are more secretocytes undergoing mitosis in breeding individuals of S. discus than in non-breeders and analysis of the faeces of the contacting fry showed that they were consuming these cells and other micro-organisms that are present on the skin of the adults.…”
mentioning
confidence: 99%
See 1 more Smart Citation